Optimization of a refrigeration system for draught beer - Joao Faria (2012)
This work aims to improve the performance of refrigeration systems to cool pressurised beverages that exist in several restaurants and bars, based on the classic vapour compression cycle. The evaporator is inserted in a tank containing iced water, where the drink from the barrel passes through a coiled heat exchanger and is cooled. The beverage, once cooled, follows upstream of a column to the tap, in order to be consumed. After reviewing several systems, it has been realized that system performance could be improved, which is the main motivation for this work. As a first stage, the refrigeration circuit of a draught beer cooling unit was monitored at various key points, using pressure, temperature and flow transducers. Additionally, the beverage circuit was also monitored with similar transducers, from the output of the barrel until the tap. Ambient temperature and energy consumed by the main components (compressor and fans) was also assessed. All data were collected through a data acquisition board to a computer, for subsequent analysis using a LabVIEW application. This paper presents preliminary results obtained within the exploratory measurements and the corresponding analysis.